PERBANDINGAN KADAR Cu (Tembaga) PADA KERANG DARAH (Anadara granosa) SEGAR DAN REBUS YANG DIJUAL DI PASAR BANJARSARI PEKALONGAN - Tri Minarsih (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Protein is a nutrient needed by humans. Marine animals is a provider of high-protein, one of the much-loved marine animals is Shell Blood. In addition to have a high content of protein, shells also have disadvantages because heavy metals can accumulate in the body, such as Cu metal. Cooking such as boiling process is expected to eliminate the toxic effects of the Cu content in the Shell Blood. In this study, samples were taken from Anadara granosa sold in markets Banjarsari Pekalongan. The method used is the Tampak spectrophotometry method, by reacting Cu with Sodium diethyltricarbonate to form complex compounds. The results of this study are: the stability of the complex 15-minute period, the maximum wavelength of 440 nm, with a regression equation: y = 0.0987 x + 0.0756 and the correlation coefficient (r) was 0.9956, and obtained blood levels of Cu in the clam fresh is 8.75 ppm, 5.95 ppm and 19.36 ppm, and after boiling for 15 min levels down to 5.39 ppm, 4.47 ppm and 15.64 ppm. Boiling is effective in lowering levels of Cu by 16-45%.